Tugas Kepemimpinan Pendidikan dalam Meningkatkan Mutu Pengelolaan Sekolah - Adelia Ashari; Mulyadi Mulyadi; Romida Arta Uli S.; Ana Husnul Hotimah; Yurika Bil Khoirin (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
School management quality is a vital factor in determining the success of the educational process, yet current efforts often appear partial and sub-optimal due to shortcomings in planning, supervision, and human resource development. This library research, employing a descriptive analytical method and systematic literature review through academic databases, aimed to analyze the crucial role of educational leadership in enhancing school management quality. The findings indicate that the core tasks of educational leadership encompass strategic planning, resource management, academic supervision, and integrated decision-making, all of which are fundamental for quality-oriented school governance. Effective leadership is characterized by vision, strong communication, adaptability, and a deep commitment to professional development. The study concludes that the success of improving school management quality is highly dependent on the principal’s ability to execute leadership tasks that are visionary, professional, strategic, and sustainable. Therefore, it is strongly recommended that principals consistently enhance their managerial and supervision competencies and cultivate a school culture that is professional and oriented towards continuous quality improvement.